Do more hats bring more benefits? Exploring the impact of dual organizational identification on work‐related attitudes and performance. Issue 3 (19th April 2013) - Chen, Yen‐Chun; Chi, Shu‐Cheng Steve; Friedman, Ray
Abstract : Recent work on organizational identity has recognized the possibility of dual identification. We present an analysis of complementary dual identification, according to which the known positive benefits of employer identification are amplified when there exist strong secondary forms of identification at work. Thus, even though non‐employer identification is weakly associated with beneficial job outcomes, these secondary aspects of non‐employer work identification remain important because they amplify the beneficial impact of employer identification on work attitudes and performance. Using a sample of sales representatives at department stores in Taiwan, we found that the stronger the department‐store identification was, the stronger the positive effects of employing‐company identification on job performance and customer‐oriented behaviour were. Practitioner points: To enhance employees' job performance and customer focus, it is important to strengthen their identification with the employing company and the workplace. The development of employees' co‐occurring identification with their workplace does not distract them from their work, but rather enhances the benefits of employing‐company identification. Companies should train their managers to be aware of employees' dual identification and of methods for strengthening it. Sales representatives at department stores and in other contexts should be granted a pleasant and attractive work environment, as the benefits of dual identification can be boosted when employees identify with their workplace.